Quantum dynamics simulations in an ultraslow bath using hierarchy of stochastic Schrödinger equations. (18th April 2018) - Ke, Yaling; Zhao, Yi
ABSTRACT: The hierarchy of stochastic Schrödinger equation, previously developed under the unpolarised initial bath states, is extended in this paper for open quantum dynamics under polarised initial bath conditions. The method is proved to be a powerful tool in investigating quantum dynamics exposed to an ultraslow Ohmic bath, as in this case the hierarchical truncation level and the random sampling number can be kept at a relatively small extent. By systematically increasing the system–bath coupling strength, the symmetric Ohmic spin-boson dynamics is investigated at finite temperature, with a very small cut-off frequency. It is confirmed that the slow bath makes the system dynamics extremely sensitive to the initial bath conditions. The localisation tendency is stronger in the polarised initial bath conditions. Besides, the oscillatory coherent dynamics persists even when the system–bath coupling is very strong, in correspondence with what is found recently in the deep sub-Ohmic bath, where also the low-frequency modes dominate. Abstract :